2016
DOI: 10.1089/mdr.2015.0064
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Profile ofStaphylococcus epidermidisandStaphylococcus haemolyticusIsolated from Blood Cultures to Vancomycin and Novel Antimicrobial Drugs over a Period of 12 Years

Abstract: The aim of this study was to evaluate the antimicrobial susceptibility profile of 85 Staphylococcus epidermidis and 84 Staphylococcus haemolyticus strains isolated from blood cultures to oxacillin, vancomycin, tigecycline, linezolid, daptomycin, and quinupristin/dalfopristin over a period of 12 years. S. epidermidis and S. haemolyticus isolated from blood cultures of inpatients, attended at a teaching hospital, were analyzed for the presence of the mecA gene and by SCCmec typing. The minimum inhibitory concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
3
4
1
Order By: Relevance
“…SCC mec types have been characterized in 31 MR-CoNS isolates, as shown in Table 1, and SCC mec type II was the dominant type of S. haemolyticus (62.5%). The results of this study are similar to those of Pinheiro et al, who demonstrated the association between SCC mec type II and S. haemolyticus isolated from blood cultures [33]. In contrast, Ruppe et al demonstrated that SCC mec type V is preferentially associated with S. haemolyticus strains isolated from disparate geographical areas such as Cambodia, Algeria, Mali, and Moldova [34].…”
Section: Discussionsupporting
confidence: 89%
“…SCC mec types have been characterized in 31 MR-CoNS isolates, as shown in Table 1, and SCC mec type II was the dominant type of S. haemolyticus (62.5%). The results of this study are similar to those of Pinheiro et al, who demonstrated the association between SCC mec type II and S. haemolyticus isolated from blood cultures [33]. In contrast, Ruppe et al demonstrated that SCC mec type V is preferentially associated with S. haemolyticus strains isolated from disparate geographical areas such as Cambodia, Algeria, Mali, and Moldova [34].…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the SCC mec types, it was observed that the type IV was prevalent in BSI isolates ( p  = 0.007), while the type III was detected only in two of them, in contrast with the study of Pinheiro and coworkers [46] that detected 53.2% of their MRSE isolates from blood cultures carrying the SCC mec type III. However, the high frequency of the SCC mec IV in clinical isolates of S. epidermidis was already observed previously [4749], demonstrating that this SCC mec type has become a common occurrence among hospital isolates.…”
Section: Discussioncontrasting
confidence: 58%
“…This two-stage assay was 100% in agreement with the reference method (Kloos & Schleifer (1975) and Bannerman (2003) [4]. Many investigators have employed this strategy for species-level identification of CoNS [14][15][16].…”
Section: Discussionsupporting
confidence: 65%